A Study of Thyroid Hormone Levels in Beetal Goats During Different Development Stages - Madan, Jyotsna; Kumar, Sandeep; Sindhu, Sonia; Gupta, Meenakshi; Pandey, Anand Kumar; Yadav, Abhay Singh; Rose, Manoj Kumar (International Journal of Bio-resource and Stress Management, 2019)
The present study was investigated on age associated variations in thyroid hormones in male and female Beetal goats. Blood samples were collected at different age groups viz. 15 days, 1 month, 2 months, 3 months and then at three-month interval until 24 months age. The plasma was analysed for tri-iodothyronine (T3) and thyroxine (T4). The T3 levels in male goats were significantly higher (p<0.05) at 15 days (1.80±0.19 ng ml-1), 6 months (1.45±0.16 ng ml-1) and 12 months (1.49±0.05 ng ml-1) of age than that found at different ages till 24 months age. Likewise, the mean T3 levels in female goats had significantly higher (p<0.05) at 15 days (1.92±0.17 ng ml-1) and 6 months (1.69±0.23 ng ml-1) of age than that found at different ages upto24 months age. The mean T4 levels in male goats were significantly (p<0.05) higher for 2 months (70.60±6.19 ng ml-1), 3 months (64.00±3.14 ng ml-1) and 6 months (75.60±2.54 ng ml-1) of age than at different ages till the age of two years. The mean T4 levels in female goats were found to be significantly (p<0.05) higher for 3 month (70.20±2.54 ng ml-1) and 6 months (74.10±6.54 ng ml-1) of age than at different ages till the age of two years. There was no statistically significant difference between sexes, but in female goats, the values were non-significantly higher than male goats during respective ages. In conclusion, the significantly higher concentrations of thyroid hormones during young and growing stages in Beetal goats may have role in growth and development.